Interfacial shear strength characterisation of alkali treated bamboo bundle – polyester composites using an improved technique. (26th November 2017) - Khoo, S.J.; Johar, M.; Low, K.O.; Wong, K.J.
ABSTRACT: This study examined the influences of alkali concentration on the interfacial characteristics of bamboo–polyester. Pull-out tests were carried out using a newly designed jig to minimise the fibre breakage during clamping. Bamboo bundles were embedded at 3, 5, 7 and 10 mm and alkali concentrations ranged from 0, 1, 3, 5 to 7 wt-%. The attenuated total reflectance-Fourier transform infrared spectroscopy spectra revealed hemicelluloses was observed at ∼1030 cm −1 . The pull-out results showed that interfacial characteristics were not influenced by the embedded length. Furthermore, the highest apparent interfacial shear strength was attained at 3 wt-% concentration, with approximately three times higher compared to the untreated one. A comparison with data from the literature showed that both untreated and treated bamboo/polyester composites have the weakest interfacial bonding. Scanning electron micrographs revealed that alkali treatment has resulted in interface enhancement through chemical modification, mechanical interlocking and frictional contact.